Rationale, Design and Methodology of the Computerized Registry of Patients with Venous Thromboembolism (RIETE) - Bikdeli, Behnood; Jimenez, David; Hawkins, Mayra; Ortíz, Salvador; Prandoni, Paolo; Brenner, Benjamin; Decousus, Hervé; Masoudi, Frederick A.; Trujillo-Santos, Javier; Krumholz, Harlan M.; Monreal, Manuel; for the RIETE Investigators (Thrombosis and Haemostasis, 2018)
Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a preventable cause of in-hospital death, and one of the most prevalent vascular diseases. There is a lack of knowledge with regards to contemporary presentation, management and outcomes of patients with VTE. Many clinically important subgroups (including the elderly, those with recent bleeding and pregnant patients) have been under-represented in clinical trials. Furthermore, design of clinical trials is challenging in some scenarios, such as in those with hemodynamically unstable PE. RIETE (Registro Informatizado Enfermedad TromboEmbolica) is a large prospective multinational ongoing registry, designed to address these unmet needs using representative data from multiple centres. Initiated in Spain in 2001, RIETE currently includes 179 centres in 24 countries and has enrolled more than 72,000 patients. RIETE has helped characterize the pattern of presentation and outcomes of VTE, including the aforementioned understudied subgroups. RIETE has recently expanded to collect long-term outcome data, and has broadened its inclusion criteria to enrol other forms of venous thrombosis (such as cerebral vein thrombosis and splanchnic vein thrombosis). The RIETE platform is also being used to conduct pragmatic comparative effectiveness studies, including randomized trials. Future steps would focus on collaboration with additional centres across the world, and efforts to ensure the quality and expansion of the registry. In conclusion, RIETE is a large ongoing registry of patients with VTE and other thrombotic conditions. Its results could be helpful for improving our understanding of the epidemiology, patterns of care and outcomes of patients with thrombotic disease.
Keywords: venous thrombosis; deep vein thrombosis; pulmonary embolism